Subclass of Multivalent Harmonic Functions Defined by Wright Generalized Hypergeometric Functions. (24th October 2013) - Aouf, M. K.; Moustafa, A. O.; Adwan, E. A.
Abstract : We introduce a new class of multivalent harmonic functions defi ned by Wright generalized hypergeometric function. Coefficient estimates, extreme points, distortion bounds, and convex combination for functions belonging to this class are obtained.